Removal of hazardous dye from aqueous media using low‐cost peanut (Arachis hypogaea) shells as adsorbents. (18th December 2020) - Herbert, Arpan; Kumar, Upendra; Janardhan, Prashanth
Abstract: In the present article, an attempt is made for simple, low‐cost, and efficient removal of Auramine dye using peanut ( Arachis hypogaea ) shells as adsorbents. Two different forms of adsorbents distilled water washed peanut shells (DPS) and NaOH treated peanut shells (NPS) were used as adsorbents. Both the adsorbents were studied using BET, pHPZC, FTIR, SEM, TGA, and XRD characterization techniques. Adsorption parameters such as effect of contact time, pH, initial dye concentration, adsorbent dose, and temperature were also assessed. Isotherm analysis at optimum conditions showed Langmuir fitted better with a q m value of 96.15 mg/g for DPS and 294.12 mg/g for NPS; while in kinetic analysis, pseudo‐second order was superior. Thermodynamics study stated that adsorption process was endothermic in nature. Overall outcomes establish that the two forms of peanut shells, DPS, and NPS were excellent in removal of Auramine dye and are low cost also as preparation cost of DPS and NPS is 68.73 INR and 106.19 INR per kg, respectively. Practitioner points: Removal of Auramine dye from aqueous media using different forms of peanut ( Arachis hypogaea ) shells as adsorbents is discussed. q m (Langmuir) using DPS and NPS were found to be 96.15 and 294.12 mg/g, respectively. Preparation cost of DPS was 68.73 INR per 1 kg, whereas for NPS it was 106.19 INR per 1 kg. Abstract : Removal of Auramine O using DPS and NPS and its results.